2015
DOI: 10.7120/09627286.24.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of Dutch broiler and pig farmers to convert to production systems with improved welfare

Abstract: The present study investigated 15 broiler and 13 fattening pig farmers' willingness-to-convert to alternative production systems with higher animal welfare standards compared to conventional production systems in The Netherlands, and explored the main barriers to the adoption of these alternative systems. Alternative production systems were categorised, according to whether farmers were required to make reversible or irreversible changes to the current farm. Two out of the four pig systems in the study were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Studies Table 9 β coefficients for the production systems in each sector, estimated from the multivariate stepwise regression of stochastic variables values on CDRM-1 Broiler production systems on the economic potential of organic systems similarly found that the organic price premium is a decisive factor in farmers' income for these systems (Kerselaers et al, 2007). A survey of broiler and fattening pig farmers indicated that the majority of farmers would not convert to alternative systems if the extra costs due to higher AW standards were not compensated, i.e., in the absence of a price premium (Gocsik et al, 2015). When price premiums are absent, farmers will only convert to those systems which are economically feasible.…”
Section: Discussionmentioning
confidence: 94%
“…Studies Table 9 β coefficients for the production systems in each sector, estimated from the multivariate stepwise regression of stochastic variables values on CDRM-1 Broiler production systems on the economic potential of organic systems similarly found that the organic price premium is a decisive factor in farmers' income for these systems (Kerselaers et al, 2007). A survey of broiler and fattening pig farmers indicated that the majority of farmers would not convert to alternative systems if the extra costs due to higher AW standards were not compensated, i.e., in the absence of a price premium (Gocsik et al, 2015). When price premiums are absent, farmers will only convert to those systems which are economically feasible.…”
Section: Discussionmentioning
confidence: 94%
“…Reluctance to implement welfare improvement strategies is associated with the perception that they are ineffective, not financially feasible, or difficult to practically manage (Fredriksen and Nafstad, 2006). Motivation is limited when farmers distrust the economic advantages of implementing strategies or when the benefits are simply unknown (Bock and van Huik, 2007;Gocsik et al, 2015). Motivation is also reduced by a perceived lack of time, skilled labour (Morgan-Davies et al, 2006), or knowledge (de Lauwere et al, 2012).…”
Section: The Gap Between Research and Practicementioning
confidence: 99%
“…Steps to reduce lameness may require farmers to change production conditions and management practices that otherwise exacerbate the problem. In this context, the cost and benefits of adopting new practices may be of importance for farmers (Gocsik et al, 2015). Besides the extrinsic characteristics of a new practice, psychological aspects such as farmers' perception of its relative advantage play a significant role in its adoption (Rogers, 1995;Adrian et al, 2005).…”
Section: Introductionmentioning
confidence: 99%